Pengembangan Modul Pelatihan Menyusui 10-Jam untuk Tenaga Awam ("Dasa Wisma") sebagai Pendamping untuk Meningkatkan Keberhasilan Pemberian ASI Eksklusif - Irmawati; Rizkiyatul Amalia; Adhani Windari (Jurnal Penelitian Pendidikan IPA, 2023)
Many studies have been conducted on the assistance of trained lay personal to increase exclusive breastfeeding. Currently, the modules used to train lay personnel is limited. The existing modules were for counsellor training with several hours and long sessions, so they were not suitable for lay         personnel who do not have a health education background. This study aims to develop and analyze the effectiveness of the 10-hour breastfeeding training module (BTM) to increase knowledge and practice                                    of lay personal. The research is carried out using Content Validity Ratio (CVR) formula by Lawshe-method to validate of the 10-hour BTM and using a pre-post-test design to analyze the effectiveness of the 10-hour BTM to increase knowledge and practice                                    of lay personal. The results show that the module has a CVR score (0.71-1.00) and a CVI score (0.84). The Paired t-test shows the module significantly increased the knowledge (p=0.001 d=3.02) and practice (p=0.001 d=1.92). Learning media that are in accordance with the characteristics of students are very important to pay attention to convey information appropriately, so that the learning process runs optimally. It was be conclude that the 10-hour BTM is suitable for increasing knowledge and practice for lay person who will assist the breastfeeding mother.